RADIOCARBON DATING OF A VERY OLD AFRICAN BAOBAB FROM SAVÉ VALLEY, ZIMBABWE - PATRUT, Adrian; RAKOSY, Laszlo; PATRUT, Roxana T.; RAŢIU, Ileana-Andreea; FORIZS, Edit; LÖWY, Daniel A.; MĂRGINEANU, Dragoș; REDEN, von, Karl F. (Studia Universitatis Babeș-Bolyai Chemia, 2016)
The article reports the radiocarbon investigation results of the Humani Bedford baobab, an old African baobab from Savé Valley, Zimbabwe. Two wood samples were collected from the large inner cavity. Several segments were extracted from these samples and analysed by AMS (accelerator mass spectrometry) radiocarbon dating. We found that the age values of segments increase with the distance into the wood. This major anomaly is characteristic to multi-stemmed baobabs with a closed ring-shaped structure and a false cavity inside. The investigation of the Humani Bedford baobab evinced that the baobab consists of three fused stems. The fourth stem of the ring is missing. The oldest dated segment was found to have a radiocarbon date of 1655 ± 14 bp, which corresponds to a calibrated age of 1575 ± 30 yr. The dating results show that the stems which build the ring stopped growing toward the false cavity more than 600 yr ago. By considering the position of the oldest segment in the investigated stem, we concluded that the Humani Bedford baobab is around 1800 yr old. According to our dating results, the Humani Bedford baobab becomes the oldest living African baobab.